2014
DOI: 10.1021/es502484z
|View full text |Cite
|
Sign up to set email alerts
|

Particle Emissions from a Marine Engine: Chemical Composition and Aromatic Emission Profiles under Various Operating Conditions

Abstract: The chemical composition of particulate matter (PM) emissions from a medium-speed four-stroke marine engine, operated on both heavy fuel oil (HFO) and distillate fuel (DF), was studied under various operating conditions. PM emission factors for organic matter, elemental carbon (soot), inorganic species and a variety of organic compounds were determined. In addition, the molecular composition of aromatic organic matter was analyzed using a novel coupling of a thermal-optical carbon analyzer with a resonance-enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
116
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(161 citation statements)
references
References 38 publications
17
116
1
Order By: Relevance
“…Table 3 summarizes the average source profiles of PM in excavator exhaust as derived in this study, as well as those previously reported by others for comparison. As shown in Table 3, the average fraction of total carbonaceous components for the excavators tested in this study is consistent with that for a marine engine, whereas the element fraction was lower than that for a marine engine (Sippula et al, 2014). Iron oxide is recognized as a catalyst and can promote soot burnout during combustion processes (Kasper et al, 1999).…”
Section: Average Chemical Composition Of Pm In Excavator Exhaustsupporting
confidence: 80%
See 1 more Smart Citation
“…Table 3 summarizes the average source profiles of PM in excavator exhaust as derived in this study, as well as those previously reported by others for comparison. As shown in Table 3, the average fraction of total carbonaceous components for the excavators tested in this study is consistent with that for a marine engine, whereas the element fraction was lower than that for a marine engine (Sippula et al, 2014). Iron oxide is recognized as a catalyst and can promote soot burnout during combustion processes (Kasper et al, 1999).…”
Section: Average Chemical Composition Of Pm In Excavator Exhaustsupporting
confidence: 80%
“…Iron oxide is recognized as a catalyst and can promote soot burnout during combustion processes (Kasper et al, 1999). The EC fraction of PM in the excavator exhaust is higher than that reported by Sippula et al (2014), which might be the result of a lower metal fraction in the excavators used for their study. The proportion of n-alkanes measured in this study was significantly higher than those emitted from a marine engine (4-fold) and non-road generator (6-fold) in a different study , which could be the result of different aliphatic compounds in the diesel fuels (Sippula et al, 2014).…”
Section: Average Chemical Composition Of Pm In Excavator Exhaustmentioning
confidence: 93%
“…In order to complement the quantification of lighter hydrocarbon compounds with two to three carbons, selected ion flow tube mass spectrometry (SIFT-MS) was applied, which has been recognized as a real-time analytical technique for combustion gases and components in exhaled breath (Smith and Spanel, 2010). This part of the analysis was done without pretreatments and took place immediately after the gaseous samples were taken from auxiliary engines.…”
Section: Voc Sampling and Analysismentioning
confidence: 99%
“…Although the legislation is focussed on sulfur emissions, the overall health and environmental effects depend in a complex way on the physical and chemical properties of the emissions (WHO, 2013). Several studies have been carried out to determine the detailed chemical composition of shipping emissions (Agrawal et al, 2008a, b;Moldanová et al, 2009;Murphy et al, 2009;Lyyränen et al, 1999;Cooper, 2003;Sippula et al, 2014); however, the ships emissions are still poorly characterized with respect to on-road vehicles.…”
Section: Introductionmentioning
confidence: 99%